On Roman Law in Leon Piniński’s Times and His Reflections on the Margin of the Anniversary of the Promulgation of Justinian’s Codification - Mikołajczyk, Marian; Nancka, Grzegorz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
In 1935, the 1400th anniversary of the promulgation of Justinian’s Codification was celebrated. As everywhere in Europe, in order to mark this occasion a ceremony was also held in Lviv. During the celebrations organized by the Lviv Branch of the Polish Philological Association, Leon Piniński, a professor of the University of Lviv, a former governor of Galicia and an art lover, gave a speech. In his subsequently published lecture entitled ‘On the 1400anniversary of Justinian’s codification’, the scholar not only referred to the anniversary, but also to the issues relating to the reality of his times. As this is one of the lesser-known works of the Lviv Romanist, it is worth examining his views in more detail.